A Meloidogyne incognita C‐type lectin effector targets plant catalases to promote parasitism. Issue 5 (16th September 2021) - Zhao, Jianlong; Sun, Qinghua; Quentin, Michaël; Ling, Jian; Abad, Pierre; Zhang, Xiaoping; Li, Yan; Yang, Yuhong; Favery, Bruno; Mao, Zhenchuan; Xie, Bingyan
Summary: Root‐knot nematodes, Meloidogyne spp., secrete effectors to modulate plant immune responses and establish a parasitic relationship with host plants. However, the functions and plant targets of C‐type lectin (CTL)‐like effectors of Meloidogyne incognita remain unknown. Here, we characterized a CTL‐like effector of M. incognita, MiCTL1a, and identified its target and role in nematode parasitism. In situ hybridization demonstrated the expression of MiCTL1 in the subventral glands; and in planta, immunolocalization showed its secretion during M. incognita parasitism. Virus‐induced gene silencing of the MiCTL1 reduced the infection ability of M. incognita in Nicotiana benthamiana . The ectopic expression in Arabidopsis not only increased susceptibility to M. incognita but also promoted root growth. Yeast two‐hybrid and co‐immunoprecipitation assays revealed that MiCTL1a interacts with Arabidopsis catalases, which play essential roles in hydrogen peroxide homeostasis. Knockout or overexpression of catalases showed either increased or reduced susceptibility to M. incognita, respectively. Moreover, MiCTL1a not only reduced catalase activity in vitro and in planta but also modulated stress‐related gene expressions in Arabidopsis. Our data suggest that MiCTL1a interacts with plant catalases and interferes with catalase activity, allowing M. incognita to establish a parasitic relationship with its host by fine‐tuning responses mediated by reactive oxygen species.